Analysis of the discrepancies between the vertical reference frames of Argentina and Brazil - Gomez, María Eugenia (2013)
The vertical reference frames for Argentina and Brazil present discrepancies due to their different datums and realizations. Thus, since 2008, we have started a series of activities with the aim of unifying the Argentine and Brazilian national vertical networks (NVNs). To achieve this goal, we have connected the two NVNs at three border points by using the geodetic levelling approach. Additionally, the gravity field approach was also applied, based on a suitable representation of the geoid by considering the Earth GravitationalModel (EGM2008) in its full resolution. In this regard, 1266 co-located Global Positioning System (GPS) and levelling benchmarks regularly distributed over Argentina (612) and Brazil (654) were considered. The geodetic levelling approach shows an offset value of 54 cm, which implies that the Argentine vertical reference frame is above that of the Brazilian vertical reference frame. However, the result of the gravimetric approach shows an offset of 57 cm, which implies a difference of approximately 3 cm between both methods. Hence, since Brazil and Argentina represent a significant part of South America, the solution to the datum problem between both countries could point towards a common vertical reference frame for the Atlantic side.